Diagnostics of rotational displacements in the shin fractures and a comparative assessment of the possibilities of three circular devices for external fixation for elimination of them - Martel, Ivan; Shved, Sergey; Matsukatov, Fedor (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
Objective: To develop a method of diagnostics of direction and magnitude of rotational displacement under conditions of shin bone fractures and to compare opportunities of the apparatus of Ilizarov, Taylor and Matsukidis-Shevtsov to eliminate them. Methods: CT scanning of shins in 25 healthy individuals (11 women, 14 men) aged from 18 to 65 years. There was made a graphic analysis of transverse sections of the tibia reproducing every 5 mm from the knee to the ankle joint. For comparative analysis of capabilities of external fixation devices we selected three representative group of 49 patients whom osteosynthesis of shin fractures type A1 with Ilizarov apparatus (21 people), Taylor (7) and Matsukidisa-Shevtsova (21) performed in. The direction and magnitude of the rotational displacement we determined according to the developed method and performed their correction after that. We compared duration of manipulation carried out and accuracy of elimination of rotational displacement. Results: There were revealed consistent patterns of change in the width of the X-ray shadow of the distal tibia fragments depending on the direction of its rotation turnround. There was developed a method for diagnostics of orientation of rotational displacements and derived mathematical formula for calculating of their value. For ease of use the author’s method of assessment of rotational displacements in the clinical setting there was proposed a template method for estimation of its parameters. There was not found significant differences in the length and precision of manipulations for elimination of rotational displacements between the Ilizarov and Taylor apparatus, and duration of similar action with Matsukidis-Shevtsov apparatus was almost in ten times less with much more accurate correction terms. Conclusion: The proposed method makes it possible to accurately determine the magnitude and direction of the rotational displacement of the tibia fracture and the Matsukidis-Shevtsov apparatus has the best opportunities to eliminate them.